Investing in long-term customer relationships - Arthur Fishman; Ziv Hellman; Avi Weiss (Bar-Ilan University, Department of Economics, 2016)
In many markets consumers form long-term relationships with firms. In such settings, a firm's existing customers are valuable assets whose "loyalty" must be maintained through continued investment. In this paper we assume that consumer loyalty is strengthened with repeated buying but may erode if the relationship is interrupted. In this context we show how a firm's history of costs and sales and the size of its customer base determine the extent to which it invests in maintaining its long term customer relationships by satisfying demand even when this involves a short-term loss. In particular, our model shows that very young firms with small customer bases will prefer losing customers in the short run to absorbing losses in high cost periods, middling sized firms will take the opposite position, absorbing losses for the sake of continuing to build customer bases, while established firms with very large customer bases revert to a willingness to lose customers in the short run.
Keywords: 330